Developing Critical Thinking Skills Through Mindfulness Oriented Biology Learning Models - Maulina, Dina; Rakhmawati, Ismi; Supriyadi, Supriyadi (Jurnal Pendidikan Sains Indonesia, 2025)
The development of critical thinking skills (CTS) is essential for students to succeed in biology learning. This study investigates the effectiveness of mindfulness-oriented learning models in fostering CTS among high school biology students. Employing a quasi-experimental design, two groups of students participated in biology lessons: the experimental group engaged in mindfulness-based activities integrated into the curriculum, while the control group received conventional instruction. Data was collected using standardized CTS assessments and student reflection journals. The findings indicate that students exposed to mindfulness-oriented learning models demonstrated significant improvements in CTS compared to those in the control group. The integration of mindfulness practices not only enhanced students analytical and evaluative abilities but also promoted greater engagement and self-awareness during biology learning. These results suggest that mindfulness-oriented models hold promise as innovative pedagogical approaches for advancing CTS in biology education. Implications for curriculum design and future research directions are discussed